Chinese eLearners eLearning - Tong, Wang; Crook, Charles (Proceedings of the International Conference on Networked Learning, 2006)
We describe the study practices and experiences of undergraduate students taking English Language in the format of an online distance learning programme. Thirty two second year students kept detailed diary records of their learning: describing the timing of each private study episode. as well as the resources they drew upon for that study. On a weekly basis, they recorded reflections regarding their recent progress: responding to both free-format and Likert-style prompts. Finally, these diary records furnished the grounding for a series of one-to-one interviews. It is shown how research material of this kind can usefully contribute to the design challenges of elearner support.